Analisis Kebijakan Pemerintah Provinsi DKI Jakarta dalam Mengatasi Permasalahan Transportasi di Perkotaan - Mu’allimah Mu’allimah; Raina Nurvita Mashpufah (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2021)
Transportation problems often arise in the midst of the rapid development of a region. The problem of transportation in urban areas that often occurs is traffic density caused by the volume of vehicles that are not balanced with road capacity. This imbalance can later lead to congestion points in urban areas. Various efforts have been made by the DKI Jakarta government in overcoming traffic jams. This study intends to analyze the effectiveness of policies that have been set by the government in overcoming transportation problems. The research method used is descriptive qualitative. This research comes from data sources in the form of scientific journals, book literature, official websites which are described through descriptive analysis, namely describing the implementation of odd-even policies, MRT project development policies, and development of Transjakarta